Analisis Stimulus Respon Peserta Didik Melalui Penerapan Teori Belajar Behavioristik Untuk Meningkatkan Prestasi Belajar - Wahyu Almizri; Neviyarni Neviyarni (Jurnal Family Education, 2023)
This study aims to describe the stimulus response analysis of students through the application of behavioristic theory to improve learning achievement. This can be a reference for teachers, both counseling teachers and subject teachers in stimulating student response stimuli through behavioristic theory. In this study, researchers used a literature study by utilizing several sources of journals and modules that the authors found. In the technique of data analysis, the researcher uses annotated bibliography analysis. This research leads to recommendations for teachers to be able to understand and know the application of behavioristic theory to stimulate student response stimuli because it is important to understand that every human being has different characteristics and learning styles. Therefore, through this writing the teacher can see the diversity of students' learning styles and then choose the right stimulus so that the responses given by students are also as expected. Keywords: behavioristic theory, learning style, counseling.